2019
DOI: 10.5114/biolsport.2019.83007
|View full text |Cite
|
Sign up to set email alerts
|

Performance profile and game-related statistics of FIBA 3x3 Basketball World Cup 2017

Abstract: The study aimed to characterize the performance profile of 3x3 basketball and particularly to assess: a) the differences between games in live time (LT) and stoppage time (ST) phases and their ratio, and b) the game-related statistics and derived game indicators differentiating between winning and losing teams. Eight games [quarterfinals, semifinals and finals (1 st and 3 rd place)] of the FIBA 3x3 basketball world cup (Serbia, 17 th -21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 21 publications
3
36
2
2
Order By: Relevance
“…19 The large percentage of time spent at high internal intensities may be a result of the little recovery time afforded to players during competition. In a recent study, Conte et al., 7 observed that stoppages during 3 × 3 basketball were typically less than 20 seconds in duration, indicating a very short time for physiological recovery during play. Physical preparation of 3 × 3 basketball athletes should therefore include exposure to high internal intensities that mimic those of gameplay to ensure such intensities can be sustained.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…19 The large percentage of time spent at high internal intensities may be a result of the little recovery time afforded to players during competition. In a recent study, Conte et al., 7 observed that stoppages during 3 × 3 basketball were typically less than 20 seconds in duration, indicating a very short time for physiological recovery during play. Physical preparation of 3 × 3 basketball athletes should therefore include exposure to high internal intensities that mimic those of gameplay to ensure such intensities can be sustained.…”
Section: Discussionmentioning
confidence: 96%
“…7,24,40 Differences in methodologies may account for the variation in work to rest ratios within the literature. For example, Conte et al., 7 defined a work to rest ratio using live time (ball in play) and stoppage time (ball out of play) in 3 × 3, whilst Ben Abdelkrim et al., 40 defined rest as walking, jogging and low-intensity shuffling, and work as all other activities in 5 × 5 basketball. The present study used time on the court as a marker of work, and time on the bench as rest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations